Serum vitamin E level and gestational diabetes mellitus: a systematic review and meta-analysis - Sharifipour, Foruzan (J Diabetes Metab Disord, 2020)
PURPOSE: Gestational diabetes mellitus (GDM) is one of the most common medical complications in pregnancy. This systematic review aimed to evaluate the association between vitamin E and GDM. METHODS: Relevant articles from the Cochrane Library, PubMed, Scopus, Science Direct, Web of Science, and EMBASE databases up to December 2019 were searched. The inclusion criteria were observational full-text articles. The fixed and random effect models were used to analyze the pooled data using Review Manager 5.3. RESULTS: Thirteen studies, including 596 participants, of whom 285 were diagnosed with GDM were included in the meta-analysis. The vitamin E level was significantly lower in women with GDM (MD: - 0.10; 95% CI: [−0.15, − 0.05]). The level of vitamin E was not different between overweight women with GDM and healthy pregnant women (MD: 0.03; 95% CI: [−0.08, 0.013]). The level of vitamin E was significantly lower in the third trimester of pregnancy in GDM women in comparison to the healthy pregnant women(MD: -0.09; 95% CI: [−0.12, −0.06]). CONCLUSION: This study showed that the level of vitamin E is significantly lower in GDM women compared to healthy pregnant women. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40200-020-00582-5) contains supplementary material, which is available to authorized users.